Smart Objects and Technologies for Social Goods - Pires, Ivan Miguel; Zdravevski, Eftim; Garcia, Nuno Cruz (Springer Nature, 2023)
This book constitutes the refereed post-conference proceedings of the 8th EAI International Conference on Smart Objects and Technologies for social Goods, GOODTECHS 2022, held in Aveiro, Portugal, in November 16-18, 2022 The 7 full papers presented were selected from 18 submissions and issue design, implementation, deployment, operation, and evaluation of smart objects and technologies for social good. Social goods are products and services provided through private enterprises, government, or non-profit institutions and are related to healthcare, safety, sports, environment, democracy, computer science, and human rights.